Mechanical Control of Whole Body Shape by a Single Cuticular Protein Obstructor-E in Drosophila melanogaster. - Reiko Tajiri; Nobuhiro Ogawa; Haruhiko Fujiwara; Tetsuya Kojima (PLoS Genetics, 2017)
Body shapes are much more variable than body plans. One way to alter body shapes independently of body plans would be to mechanically deform bodies. To what extent body shapes are regulated physically, or molecules involved in physical control of morphogenesis, remain elusive. During fly metamorphosis, the cuticle (exoskeleton) covering the larval body contracts longitudinally and expands laterally to become the ellipsoidal pupal case (puparium). Here we show that Drosophila melanogaster Obstructor-E (Obst-E) is a protein constituent of the larval cuticle that confers the oriented contractility/expandability. In the absence of obst-E function, the larval cuticle fails to undergo metamorphic shape change and finally becomes a twiggy puparium. We present results indicating that Obst-E regulates the arrangement of chitin, a long-chain polysaccharide and a central component of the insect cuticle, and directs the formation of supracellular ridges on the larval cuticle. We further show that Obst-E is locally required for the oriented shape change of the cuticle during metamorphosis, which is associated with changes in the morphology of those ridges. Thus, Obst-E dramatically affects the body shape in a direct, physical manner by controlling the mechanical property of the exoskeleton.